Kombinasi Naa Dan Tdz Dengan Berbagai Taraf Konsentrasi Dalam Kultur In Vitro Tanaman Pisang Cavendish (Musa Acuminata C.) - Wisesa , Cindekia Purba; Asih, Pitri Ratna; Farmia, Asih (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2022)
The objective of the study is to obtain best composition of Plant Growth RegulatorTDZ and NAA for 1.) shoot multiplication, 2.) root formation of cavendish banana using in vitro methods. This research was conducted at Biotechnology Laboratory of Agriculture Development Polytechnic Yogyakarta-Magelang Department of Agriculture. This research was carried out from 27th January to 20th April 2022. The experimental design was factorial design that consisted of two factors and arranged in Completely Randomized Design with five replicates. The first factor was medium containing TDZ with four levels of concentration, these are 0 ppm, 0,1 ppm, 0,2 ppm, and 0,3 ppm. The second one was medium containing NAA with four levels of concentration, these are 0 ppm, 0,4 ppm, 0,8 ppm, and 1,2 ppm. The data were analysed using analysis of variance (ANOVA) and tested for significancy using DMRT 5%. The result indicated that medium which containing TDZ 0,3 ppm and NAA 0,4 ppm have the best effect for shoot multiplication in cavendish banana comparing to other treatment. Furhermore, medium that containing NAA 1,2 ppm have the best effect for root formation in cavendish banana comparing to other treatment.